Long-term chromospheric activity of non-eclipsing RS CVn-type stars chromospheric activity of non-eclipsing RS CVn-type stars - Buccino, Andrea Paola (2009)
Context: The IUE database provides a large number of UV high and low-resolution spectra   of RS CVn-type stars from 1978 to 1996. In particular, many of these stars were monitored  continuously during several seasons by IUE. Aims: Our main purpose is to study the short  and long-term chromospheric acti- vity of the RS CVn systems most observed by IUE: HD  22468 (V711 Tau, HR 1099, K1IV+G5V), HD 21242 (UX Ari, K0IV+G5V) and HD  224085 (II Peg, K2IV). Methods: We  first obtain the Mount Wilson index S from the IUE  high and low- resolution spectra. Secondly, we analyse with the Lomb-Scargle periodogram  the mean annual index S and the amplitude of the rotational modulation of the index S. Results: For HD 22468 (V711 Tau, HR 1099), we found a possible chromospheric cycle  with a period of  18 years and a shorter cycle with a period of  3 years, which could be associated to a chromospheric "flip- flop" cycle. The data of HD 224085 (II Peg) also suggest a chromospheric cycle of  21 years and a  flip- flop cycle of  9 years. Finally, we obtained a possible chromospheric cycle of  7 years for HD 21242 (UX Ari).